Pengaruh Penggunaan Aplikasi Assemblr Edu Terhadap Hasil Belajar IPA SDN Gugus III Kota Bengkulu - Rahmawati, MSY. Isye Aulia; Noperman, Feri; Kurniawati, Ike (Universitas Bengkulu, 2024)
This study seeks to examine how the utilization of the Assemblr EDU application impacts the academic performance of fifth-grade students in thematic science subjects within Cluster III Elementary Schools in the City of Bengkulu. Employing a quantitative approach, the research adopts a quasi-experimental design known as The Matching Only Pretest-Posttest Control Group Design. The study population comprises fifth-grade students from Cluster III Elementary Schools in Bengkulu, with the sample selected via Cluster Random Sampling. Specifically, students from State Elementary School 57 form the experimental group, while those from State Elementary School 17 constitute the control group. Data collection involves administering a written test consisting of 10 multiple-choice questions as both pretest and posttest measures. Following the analysis of posttest scores, the obtained significance value (sig. 2-tailed) falls below 0.05, indicating a discernible difference in posttest outcomes between the experimental and control groups. Consequently, it can be inferred that the utilization of the Assemblr EDU application correlates with enhanced learning outcomes in thematic science subjects among fifth-grade students in Cluster III Elementary Schools in Bengkulu.